Black in the British Frame: The Black Experience in British Film and Television - Bourne, Stephen (Bloomsbury Publishing Plc, 2005)
In this updated edition of his acclaimed and award-winning study, Stephen Bourne takes a personal look at the history of black people in popular British film and television. He documents, from original research and interviews, the experiences and representations which have been ignored in previous media books about people of African descent. There are chapters about Paul Robeson, Newton I. Aduaka, soap operas and much more - as well as several useful appendices and suggestions for further reading.
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Étude de la réception; 2-Étude des représentations; 3-Europe (corpus analysé); 4-Europe (lieu de production du savoir); Royaume-Uni (corpus analysé); Royaume-Uni (lieu de production du savoir); _Nettoyé